Entrepreneurship in emerging markets: mapping the scholarship and suggesting future research directions - Inkizhinov, B.; Gorenskaia, E.; Nazarov, D.; Klarin, Anton (2020)
Purpose: To provide a comprehensive systematic review of entrepreneurship in the context of emerging markets (EMs). The area of research is topical considering the rise of EMs on the global scene and the importance of entrepreneurship in the development of EMs.